Prospective, cross-sectional study, demonstrating efficacy of blue fixation target while recording Pattern Visual Evoked Potential in optic neuropathy - Vincent, Ajoy; Shetty, Rohit; Kurian, Mathew; Shetty, Bhujang K. (Documenta ophthalmologica, 2009)
To report the efficacy of a blue fixation target to record Pattern Visual Evoked Potential (PVEP) in optic neuropathy subjects with acquired red-green (RG) color vision deficit. This is a prospective, nonrandomized, cross-sectional, case series of twenty-nine eyes of twenty-two subjects with optic neuropathy of various etiologies. All underwent detailed ophthalmological evaluation, imaging, and PVEP. PVEP was done with 120′ and 60′ checker stimulus to both red and blue fixation targets. The amplitude and latency of P100 waveform was the measured outcome. The PVEP recording to blue fixation target was found to be superior to the red fixation target in cases of RG color vision deficits with both 120′ ( P = 0.01) and 60′ ( P = 0.037) check sizes. In the cases in which the PVEP was recordable with both red and blue fixation targets, the P100 amplitude and latency parameters were comparable and showed positive correlation. Defective fixation and abnormal RG color vision also affected PVEP recordability to the red fixation target. Good fixation is essential for obtaining a reliable PVEP recording. In this study, the authors have used a blue fixation target as a method to ensure fixation in patients with RG color deficits and have demonstrated the ability to get good recordings in cases with otherwise flat recording. The use of alternate colored target or achromatic fixation target should be considered to ensure good central fixation so as to yield better quality recording that possibly correlates better with the functioning of the optic pathway in subjects with abnormal color vision.